Study on the Numerical Simulation of Hot Rolling Forming Technology of Pinion of Spiral Bevel Gear - Tang Hongyan; Deng Xiaozhong; Gao Zhenshan; Zhang Qingjie (Jixie chuandong)
The process of hot rolling for the pinion of spiral bevel gear is simulated by using DEFORM-3D and the teeth formed process is analyzed. The simulation results show that the feasibility of rolling forming process. Based on the analysis of the physical field such as equivalent strain field,equivalent stress field,temperature field and the load-stroke curve,the parameters of rolling process are obtained.